27 Defining Grazing Recommendations for Alfalfa-Bermudagrass Mixtures in the Southeastern U.S. (28th November 2020) - Groce, Kaylyn; Tucker, Jennifer J; Mason, Katie; Marks, Landon; Mullenix, Mary K
Abstract: Recently there has been growing interest in interseeding high-quality legumes, like alfalfa, into existing bermudagrass stands as a step towards improving forage, animal, and ecosystem sustainability in the Southeast. Current work evaluating these mixtures has focused on management and production of stored forages, and limited work has evaluated the use of alfalfa-bermudagrass mixtures under grazing conditions. It is known that both grazing intensity and frequency impact overall alfalfa stand production over time. The objective of this research is to evaluate the effect of harvest height and frequency on alfalfa interseeded into bermudagrass to develop grazing management recommendations. In 2018 thirty-six alfalfa-bermudagrass plots were established at 4 locations across Alabama and Georgia in a randomized complete block design with four replications at each location. Alfalfa varieties utilized were selected for suitability to location and were either 'Bulldog 505' or 'Bulldog 805' interseeded into existing hybrid bermudagrass sods. Treatments included combinations of harvest frequency (2, 4, or 6 weeks) and harvest height (5, 10, 15 cm) and plots were evaluated to determine the optimum interval in relation to sward yield, alfalfa persistence, stand density, botanical composition, nutritive value, and change over time. Forage yield was affected by the interaction of location with harvest frequency and height (P < 0.05). At three of the four locations, overall seasonal yield from the 5cm cutting height was greatest; however, alfalfa persistence declined in these treatments throughout the season and was less than 10% at the northern locations when 2019 data collection began. Additionally, crude protein (CP) and in-vitro digestibility (IVDMD) declined throughout the season as the alfalfa presence decreased. This study is supported by funding from the USDA-NIFA-Alfalfa Forage Research Program (2017).